2005
DOI: 10.1128/jvi.79.16.10678-10689.2005
|View full text |Cite
|
Sign up to set email alerts
|

An S101P Substitution in the Putative Cleavage Motif of the Human Metapneumovirus Fusion Protein Is a Major Determinant for Trypsin-Independent Growth in Vero Cells and Does Not Alter Tissue Tropism in Hamsters

Abstract: Human metapneumovirus (hMPV), a recently described paramyxovirus, is a major etiological agent for lower respiratory tract disease in young children that can manifest with severe cough, bronchiolitis, and pneumonia. The hMPV fusion glycoprotein (F) shares conserved functional domains with other paramyxovirus F proteins that are important for virus entry and spread. For other paramyxovirus F proteins, cleavage of a precursor protein (F 0 ) into F 1 and F 2 exposes a fusion peptide at the N terminus of the F 1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 67 publications
5
65
1
Order By: Relevance
“…RSV F protein activation requires cleavage at two distinct furin sites (25), in contrast to the single furin site present in most F proteins. The HMPV F protein from the majority of strains lacks the ability to be efficiently processed by cellular proteases (47) and must undergo cleavage by extracellular proteases prior to fusion triggering. The absence of HMPV F protein proteolytic processing by intracellular proteases would provide additional control of triggering, preventing the premature activation of F protein in the lower pH environment of the secretory pathway prior to viral assembly.…”
Section: Discussionmentioning
confidence: 99%
“…RSV F protein activation requires cleavage at two distinct furin sites (25), in contrast to the single furin site present in most F proteins. The HMPV F protein from the majority of strains lacks the ability to be efficiently processed by cellular proteases (47) and must undergo cleavage by extracellular proteases prior to fusion triggering. The absence of HMPV F protein proteolytic processing by intracellular proteases would provide additional control of triggering, preventing the premature activation of F protein in the lower pH environment of the secretory pathway prior to viral assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage takes place at a mono-or multibasic cleavage site immediately upstream of a hydrophobic fusion peptide, generating two polypeptide chains (F2 N-terminally located to F1) that remain covalently linked by at least one disulfide bond. It has been reported that the hMPV F protein has a monobasic cleavage site that can be recognized by trypsin (30,32) or by TMPRSS2 (35), a transmembrane serine protease present in the human airway epithelium. The ectodomain of paramyxovirus F proteins also contains two conserved heptad repeat (HR) regions, designated HRA and HRB, which are located downstream of the fusion peptide and upstream of the transmembrane (TM) domain, respectively.…”
mentioning
confidence: 99%
“…2C). These results suggested that cell lines that maintain lasting hMPV genome replication could be obtained, especially if the cytopathic effect (CPE) of the virus could be kept minimal, for example, under conditions where the fusion activity of the viral envelope proteins is minimized by avoiding exposure to trypsin (4,70,84). To select cells that harbored replicating hMPV genomes, we fused the GFP marker to the PAC protein that confers resistance to puromycin.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the full-length viral genome in these cultures was also demonstrated by the ability to rescue virions, capable of a single cycle of infection, by the ectopic coexpression of wild-type M proteins in the selected cells. Several factors may account for the successful generation of our improved reverse genetics system, including the generation of a single plasmid that carries all four TRC genes instead of the use of four separate expression plasmids and the ability to minimize the CPE of the virus by growing the hMPV-expressing cells in serum-containing medium and in the absence of trypsinization conditions that reduce the fusogenic activity of the F protein (4,70,84). However, it should be noted that even under these conditions, the initial number of surviving colonies was relatively small (about 10 colonies for each transfection).…”
Section: Discussionmentioning
confidence: 99%